2021
DOI: 10.3168/jds.2020-19584
|View full text |Cite
|
Sign up to set email alerts
|

The hidden cost of disease: I. Impact of the first incidence of mastitis on production and economic indicators of primiparous dairy cows

Abstract: Mastitis is a highly prevalent disease, which negatively affects cow performance, profitability, welfare, and longevity. The objectives of this study were (1) to quantify the impact of the first instance of mastitis, at different stages of lactation, on production and economic performance, and (2) to further quantify the impact of the first instance of mastitis when only cows that remain in the herd for at least 100 d in milk (DIM) and those that remain for 305 DIM are included in the analysis. A retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 22 publications
0
22
1
2
Order By: Relevance
“…Similar indicators can be seen in other countries, so effective mastitis control programs, including early diagnosis of mastitis, are more important than treatment (Halasa et al 2007;Polat et al 2010). Puerto et al (2021) reported that in the case of mastitic cows, the drops in production was significant due to a significant decrease in cumulative milk value (-287 to 591 Can$, -228 to -470 US$), margin over feed cost to -429 US$) and gross profit (-649 to -908 Can$, -516 to -722 US$) for mastitic cows at all stages.…”
Section: Introductionmentioning
confidence: 71%
“…Similar indicators can be seen in other countries, so effective mastitis control programs, including early diagnosis of mastitis, are more important than treatment (Halasa et al 2007;Polat et al 2010). Puerto et al (2021) reported that in the case of mastitic cows, the drops in production was significant due to a significant decrease in cumulative milk value (-287 to 591 Can$, -228 to -470 US$), margin over feed cost to -429 US$) and gross profit (-649 to -908 Can$, -516 to -722 US$) for mastitic cows at all stages.…”
Section: Introductionmentioning
confidence: 71%
“…, Pseudomonas aeruginosa and Staphylococcus aureus are common microorganisms that endanger the health of cow udders and cause mastitis [ 31 , 32 , 33 ]. Major reductions are observed in performance (cumulative milk, fat and protein yield) and gross profit for cows with mastitis [ 34 , 35 ]. Cows with mastitis also have a decreased percentage of pregnancies for first artificial inseminations and increased pregnancy loss compared with healthy cows [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bovine mastitis is a transmissible disease that decreases milk quality and yield ( 1 ). Furthermore, mastitis increases the culling rate, resulting in considerable economic losses to dairy farming worldwide ( 2 ).…”
Section: Introductionmentioning
confidence: 99%